Sodium-rich high-voltage hard carbon negative electrode material as well as preparation method and application thereof
By preparing sodium-complemented high-voltage hard carbon anode material, the problem of capacity attenuation caused by sodium ion deposition in the prior art is solved, and the high cycling performance and high capacity efficiency of the material are achieved.
Patent Information
- Application Number
- CN202411775844.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-14
AI Technical Summary
After 1200 weeks of cycle, the existing hard carbon anode material cannot be detached due to sodium ion deposition, resulting in rapid attenuation of capacity.
A sodium-enriched high-voltage hard carbon negative electrode material is used to prepare a sodium-enriched high-voltage hard carbon material, including oxygen-free pre-calcination and high-temperature calcination of hard carbon raw materials. Then, a mixed oxide solution of benzoyl peroxide, hydrogen peroxide and deionized water is used to treat the hard carbon material, and an inorganic sodium salt is added. Sodium-rich high-voltage hard carbon negative electrode material is prepared by wet ball milling, water washing, drying and airflow crushing.
By embedding sodium ions into the synaptic sites of hard carbon materials, a source of sodium ions is provided to ensure that the sodium ions can be continuously embedded and detached during charging and discharging, significantly improving the cyclic performance of the material, the capacity decays to 85% only after 2800 weeks, and the first-effect specific capacity reaches 305mAh/g.
Smart Images

Figure CN119612488A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy technology, and specifically relates to a sodium-rich high-voltage hard carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] The development of sodium-rich hard carbon anode materials is crucial for the development of new energy technologies. Sodium resources are abundant in the earth's crust and have significant cost advantages over lithium resources. The anode is the electrode where the reduction reaction occurs in the battery. In sodium-ion batteries, hard carbon is often used as the anode material. Hard carbon anode materials are ideal for sodium-ion batteries due to their high stability and reversible capacity. In terms of energy storage and release, the migration of sodium ions between the anode and the cathode enables the storage and release of electrical energy. During charging, sodium ions are released from the cathode and embedded in the cathode; during discharge, sodium ions are released from the cathode and embedded in the cathode to complete the output of electrical energy. In addition, sodium-ion batteries also perform well in low-temperature performance, safety, and fast charging capabilities, providing broad application prospects in energy storage equipment and electric vehicles. Through research and development and innovation, the limitations of traditional hard carbon materials in energy storage capacity can be overcome, the performance of sodium-ion batteries can be improved, and their commercialization process can be promoted, thereby meeting the growing demand for new materials for energy storage batteries in renewable energy generation.
[0003] The hard carbon negative electrode in the prior art is only used as a conductive material, and the common hard carbon negative electrode materials on the market will have a rapid capacity decay after 1200 cycles due to the deposition of sodium ions in the hard carbon, making it impossible to escape.
[0004] Based on the above reasons, this application is filed. Summary of the invention
[0005] Based on the above reasons, in view of the problems or defects existing in the prior art, the purpose of the present invention is to provide a sodium-rich high-voltage hard carbon negative electrode material and its preparation method and application, so as to solve or at least partially solve the above-mentioned technical defects existing in the prior art.
[0006] In order to achieve one of the above purposes of the present invention, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a sodium-supplemented high-voltage hard carbon negative electrode material, the method specifically comprising the following steps:
[0008] (1) pre-calcining the hard carbon raw material in the absence of oxygen at 500-600° C. to obtain a pre-carbonized material; then calcining the pre-carbonized material at a high temperature of 1400-1600° C., cooling to room temperature after calcination, and preliminarily crushing the calcined product to obtain a hard carbon material;
[0009] (2) Mix benzoyl peroxide, hydrogen peroxide and deionized water according to a ratio to obtain an oxidizing solution; add the hard carbon material described in step (1) to the oxidizing solution, soak it at room temperature for a period of time and then stir it; add inorganic sodium salt to the obtained mixed solution, stir it thoroughly to obtain a solid-liquid mixture; then wet ball mill the solid-liquid mixture, wash it with water, dry it, and air flow crush it to obtain the sodium-supplemented high-voltage hard carbon negative electrode material.
[0010] Furthermore, in the above technical solution, the hard carbon raw material in step (1) is at least one of coconut shell, palm, wood, resin, corn silk, etc. The selection of the hard carbon raw material is based on the following principles: the raw material humidity is less than or equal to 5%, the Mohs hardness is between 1 and 4, and the cellulose content is at least 50%.
[0011] Furthermore, in a preferred embodiment of the present invention, the hard carbon raw material is coconut shell.
[0012] Specifically, in the above technical solution, the purpose of the oxygen-free pre-calcination in step (1) is to discharge the tar in the hard carbon raw material to obtain a pre-carbonized material.
[0013] Furthermore, in the above technical solution, the time of the oxygen-free pre-calcination treatment in step (1) is 3-5 hours, preferably 4 hours.
[0014] Furthermore, in the above technical solution, during the anaerobic pre-calcination treatment in step (1), a protective gas may be introduced into the reaction system to accelerate the discharge of tar by purging with the protective gas.
[0015] Furthermore, in the above technical solution, the flow rate of the protective gas is 1-5 ml / s.
[0016] Furthermore, in the above technical solution, the protective gas is argon.
[0017] Furthermore, in the above technical solution, the time of high temperature calcination in step (1) is 3-4 hours.
[0018] Furthermore, in the above technical solution, the particle size of the calcined product after the preliminary crushing in step (1) does not exceed 500 mesh.
[0019] Furthermore, in the above technical solution, the mass ratio of benzoyl peroxide, hydrogen peroxide and deionized water in step (2) is (0.06-0.1):(0.14-0.2):(0.72-0.78).
[0020] Furthermore, in a preferred embodiment of the present invention, the mass ratio of benzoyl peroxide, hydrogen peroxide and deionized water is 0.08:0.17:0.75.
[0021] Specifically, in the above technical solution, in step (2), benzoyl peroxide is used to treat the surface of the hard carbon material, and carbon atoms can be converted into hydroxyl groups or carboxyl groups through oxidation reaction. This method is simple to operate and has low cost. In addition, the mixed oxidizing solution containing oxidants such as hydrogen peroxide used in the present invention is relatively mild and can reduce etching and damage to the structure of the hard carbon material.
[0022] Furthermore, in the above technical solution, the solid-liquid ratio of the hard carbon material to the oxidizing liquid in step (2) is 1 ml:1 g.
[0023] Furthermore, in the above technical solution, the soaking time in step (2) is 2-5 hours. In a preferred embodiment of the present invention, the soaking time is 3 hours.
[0024] Furthermore, in the above technical solution, the stirring time in step (2) is 0.5-2 hours, and the stirring speed is 100-500 r / min. In a preferred embodiment of the present invention, the stirring time is 1 hour, and the stirring speed is 200 r / min.
[0025] Furthermore, in the above technical solution, the inorganic sodium salt is a sodium salt that can contact the hydroxyl or carboxyl sites on the hard carbon material. In a preferred embodiment of the present invention, the inorganic sodium salt in step (2) is at least one of sodium carbonate or sodium hydroxide.
[0026] Furthermore, in the above technical solution, the mass ratio of the inorganic sodium salt to the hard carbon material in step (2) is (1-2):100.
[0027] The second object of the present invention is to provide a sodium-supplemented high-voltage hard carbon negative electrode material prepared by the above method.
[0028] The third object of the present invention is to provide the application of the sodium-supplemented high-voltage hard carbon negative electrode material prepared by the above method in sodium ion batteries.
[0029] The fourth object of the present invention is to provide a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein: the active material used in the negative electrode is the sodium-supplemented high-voltage hard carbon negative electrode material prepared by the above-mentioned method.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The present invention embeds sodium ions into the synaptic sites of the hard carbon material, where a sodium ion source is provided for the sodium ions to be embedded and released during the charge and discharge process. The sodium-supplemented high-voltage hard carbon negative electrode material produced by the present invention can continuously replenish sodium ions.
[0032] (2) The sodium-supplemented high-voltage hard carbon negative electrode material prepared by the present invention can modify ion channels, and the number of channels suitable for the free movement of ions is greatly increased, thereby increasing our initial specific capacity to 305 mAh / g.
[0033] (3) The purpose of introducing inorganic sodium salt in the present invention is that the reason for using this material is that it has no reducing property and will not affect the chemical reaction environment (here is the external environment, the chemical environment is such as acid and alkali, this inorganic salt is weakly acidic, so it will not hinder the chemical reaction equation). And the added inorganic sodium salt forms a chemical bond on the surface or inside of the hard carbon material through a chemical bond method, thereby stably introducing the sodium element into the hard carbon material. This method usually involves a chemical reaction between the functional groups (such as hydroxyl, carboxyl, etc.) on the surface of the hard carbon and the inorganic sodium salt. During the reaction, the sodium atoms form covalent bonds or ionic bonds with the carbon atoms or other functional groups in the hard carbon material, thereby achieving a firm bond of sodium in the hard carbon material. The chemical bond method has the advantages of strong binding force and good stability.
[0034] (4) The battery prepared using the sodium-supplemented high-voltage hard carbon negative electrode material of the present invention has excellent cycle performance. After 2800 cycles, the capacity decays to 85%. The capacity is high, reaching a gram capacity of 378 mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 This is a process flow chart for preparing the sodium-rich high-voltage hard carbon negative electrode material of the present invention;
[0037] Figure 2 This is a comparison chart of the charge and discharge curves of the sodium-rich high-voltage hard carbon negative electrode materials prepared in Examples 1-3.
[0038] Figure 3 XRD pattern of HC-B prepared in Example 2;
[0039] Figure 4 The cycle spectra of the full-battery assembled using HC-B prepared in Example 2 and HC-C prepared in Example 3;
[0040] Figure 5 This is a high-magnification SEM image of HC-B prepared in Example 2;
[0041] Figure 6This is a low-magnification SEM image of HC-B prepared in Example 2. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below through implementation cases. This implementation case is implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given to illustrate that the present invention is creative, but the protection scope of the present invention is not limited to the following implementation cases.
[0043] According to the information contained in this application, various changes can be easily made to the precise description of the present invention for those skilled in the art.It should be understood that the scope of the present invention is not limited to defined processes, properties or components, because these embodiments and other descriptions are only for illustrating specific aspects of the present invention.
[0044] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the amount, percentage, and other numerical values should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.
[0045] The equipment and raw materials used in the present invention can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0046] The deionized water used in the following embodiments of the present invention is tertiary deionized water, and its conductivity is less than 0.1 μS / cm.
[0047] Example 1
[0048] A method for preparing a sodium-rich high-voltage hard carbon negative electrode material (numbered HC-A) of this embodiment comprises the following steps:
[0049] 1. Material selection: Coconut shell is selected as the hard carbon raw material. The coconut shell raw material has a humidity of 3%, a Mohs hardness of 2.7, a cellulose content of 53.06%, a lignin content of 36.51%, and an ash content of 0.61%.
[0050] 2. Anaerobic precalcination: Take an appropriate amount of the coconut shell and place it in a tubular furnace, and heat it to 500-600°C in an argon atmosphere for pre-carbonization for 4 hours. During the pre-carbonization, continue to introduce argon protective gas flow into the tubular furnace at a rate of 3 ml per second to accelerate the discharge of tar. After the pre-carbonization is completed, a pre-carbonized material is obtained.
[0051] 3. High-temperature calcination: the pre-carbonized material is placed in an orbital furnace and heated in a stepwise manner at a heating rate of 2°C / min, and the temperature is continuously raised to 1540°C and then kept at this temperature for 3.5 hours; after the end of the heat preservation, the obtained calcined product is quickly cooled to room temperature at a temperature of 4°C / min;
[0052] 4. Take out the cooled high-temperature calcined product and coarsely crush it to a particle size of no more than 500 meshes to obtain a hard carbon material;
[0053] The following are the innovations of the present invention in modifying ordinary hard carbon materials into sodium-rich hard carbon materials:
[0054] 5. Prepare oxidizing solution: Mix benzoyl peroxide, hydrogen peroxide and deionized water in a mass ratio of 0.06:0.14:0.72 to obtain oxidizing solution.
[0055] 6. Add the hard carbon material into the oxidizing solution at a solid-liquid ratio of 1 ml:1 g, soak at room temperature for 3 hours, and then stir at 200 r / min for 1 hour to obtain a mixed solution.
[0056] 7. Add sodium carbonate to the mixed solution and stir thoroughly to obtain a solid-liquid mixture; wherein: 1.06 grams of sodium carbonate is added for every 100 grams of hard carbon material.
[0057] 8. Wet ball milling: Add 3 mm and 5 mm zirconium beads into the ball mill of the ball mill at a mass ratio of 2:1, then add the solid-liquid mixture and start ball milling, and control the speed of the ball mill to 77%-87%; let it stand after ball milling for 3 hours, and sieve to remove the zirconium beads;
[0058] Among them: the volume ratio of the total volume of zirconium beads, the volume occupied by the solid-liquid mixture, and the remaining space is 3.5:3.5:3; wherein: the remaining space refers to the spatial volume of the ball mill after deducting the volume of the zirconium beads and the volume occupied by the solid-liquid mixture from the total volume of the ball mill.
[0059] 9. Washing and drying: Filter the material after standing and screening, pour the filter residue into distilled water with a solid-liquid ratio of 1:3 for washing. After washing twice, dry it in a blast at 85°C for 4 hours.
[0060] 10. Airflow milling: After drying, the material is put into airflow milling for crushing and screening to obtain the sodium-rich high-voltage hard carbon negative electrode material (numbered HC-A).
[0061] Example 2
[0062] The preparation method of a sodium-rich high-voltage hard carbon negative electrode material (numbered HC-B) in this embodiment is basically the same as that in Example 1, with the only difference being that the mass ratio of benzoyl peroxide, hydrogen peroxide and deionized water in this embodiment is 0.08:0.17:0.75.
[0063] Example 3
[0064] The present embodiment provides a method for preparing a sodium-rich high-voltage hard carbon negative electrode material (numbered HC-C), which is basically the same as that in Example 1, except that the mass ratio of benzoyl peroxide, hydrogen peroxide and deionized water in the present embodiment is 0.1:0.2:0.78.
[0065] Performance Testing:
[0066] The HC-A, HC-B and HC-C prepared in the above Examples 1-3 were respectively used as negative electrode active materials to assemble button batteries, and the specific method was as follows:
[0067] The negative electrode sheet is composed of a composite hard carbon material, Super P conductive carbon, styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) binder, wherein the mass ratio of the composite hard carbon material, Super P, SBR and CMC is 90:2:4:4. The composite hard carbon material powder and Super P conductive carbon are ground and mixed evenly for 20 minutes in proportion, the mixed composite hard carbon material and Super P conductive carbon are mixed with SBR (49.5% aqueous solution) and CMC (2% aqueous solution), placed on a micro ball mill and stirred for 15 minutes to obtain a uniform slurry, the slurry is evenly coated on aluminum foil (the coating amount is 101.21 grams per square centimeter), vacuum dried in an oven at 120°C for 5 hours, and a negative electrode sheet with a diameter of 12 mm is punched out with a gun press, and weighed for standby use.
[0068] A sodium ion battery half-cell is formed by using a sodium sheet as the positive electrode, the negative electrode is the negative electrode sheet prepared above, the separator is a PP separator or a glass cellulose separator, and the electrolyte is a 1 mol / L sodium hexafluorophosphate solution. The test item density is 180 mA / g, the test voltage range is 0.05 volts to 2.5 volts, and the button battery is subjected to a charge and discharge cycle test.
[0069] Depend on Figure 2 It can be seen that the first discharge specific capacity of HC-A is 305mAh / g; the first discharge specific capacity of HC-B is close to that of HC-A, which is 305mAh / g, and the first discharge specific capacity of HC-C is 301mAh / g. The voltage platform of HC-A is significantly higher than that of HC-B and HC-C, and the voltage platform of HC-C is slightly higher than that of HC-B. The higher the voltage platform during the charge and discharge process, the less likely it is to reach the sodium precipitation potential. Therefore, it will be safer at the same voltage, and the material can be charged quickly with high voltage.
[0070] Figure 3 This is the XRD pattern of HC-B prepared in Example 2. From the two peaks at 27° and 43° in the XRD pattern, it can be seen that the manufactured material is a hard carbon material.
[0071] The negative electrode hard carbon material prepared by the present invention is used as the negative electrode active material of the battery to prepare a soft-package sodium ion battery, and the specific method is as follows:
[0072] Negative electrode preparation: Weigh the negative electrode active material, which is HC-B prepared in Example 2 or HC-C prepared in Example 3, mix it with polyvinylidene fluoride binder and conductive carbon black in a mass ratio of 98:6:5, and apply it on copper foil (coating amount is 101.21 g / cm2); then cut it into 4 cm × 3 cm pole pieces, and dry them in a drying oven at 120 degrees Celsius for use.
[0073] Preparation of positive electrode sheets: The positive electrode active material is prepared by mixing sodium ferric pyrophosphate with conductive carbon black and binder polyvinylidene fluoride in a mass ratio of 98:10:5.5 to form a slurry. The viscosity of the slurry is adjusted with N-methylpyrazolone. The prepared positive electrode material slurry is then coated on an aluminum foil current collector (the coating amount is 93.42 grams per square centimeter). A slitting machine is used to cut the slurry into 4 cm × 3 cm pieces. After drying, the pieces are placed in a vacuum oven at 120°C for drying and standby use.
[0074] Electrolyte preparation: In a glove box filled with argon, weigh 167.95 g of sodium hexafluorophosphate (NaPF 6 ), then slowly add sodium hexafluorophosphate into a beaker containing 1 liter of diethylene glycol dimethyl ether (DEGDME) solvent under uniform stirring, and after it is completely dissolved, 1 mol / L NaPF 6 / DEGDME electrolyte.
[0075] Battery assembly: Take the negative electrode sheet and positive electrode sheet prepared above, separate the positive and negative electrodes with a single-layer polypropylene film separator, add an appropriate amount of electrolyte, and assemble a soft-package sodium ion battery.
[0076] The assembled soft-package sodium ion battery is placed on the electrochemical platform for charge and discharge cycle testing: the voltage range is adjusted to 2 to 4 volts and tested at 1C rate. Figure 4 It can be seen that after 200 cycles, the full battery capacity is stable and has no obvious decrease, with a retention rate of 99.99%.
[0077] Figure 5 This is a high-magnification SEM image of HC-B prepared in Example 2; Figure 6 This is a low-magnification SEM image of HC-B prepared in Example 2. It can be seen that the surface of the material is densely covered with dense pores, which can provide more contact sites for the storage of sodium. Therefore, the sodium-rich high-voltage hard carbon negative electrode material prepared by the present invention has excellent electrochemical performance.
Claims
1. A method for preparing a sodium-supplemented high-voltage hard carbon negative electrode material, characterized in that: The method specifically comprises the following steps: (1) pre-calcining the hard carbon raw material in the absence of oxygen at 500-600° C. to obtain a pre-carbonized material; then calcining the pre-carbonized material at a high temperature of 1400-1600° C., cooling to room temperature after calcination, and preliminarily crushing the calcined product to obtain a hard carbon material; (2) Mix benzoyl peroxide, hydrogen peroxide and deionized water according to a ratio to obtain an oxidizing solution; add the hard carbon material described in step (1) to the oxidizing solution, soak it at room temperature for a period of time and then stir it; add inorganic sodium salt to the obtained mixed solution, stir it thoroughly to obtain a solid-liquid mixture; then wet ball mill the solid-liquid mixture, wash it with water, dry it, and air flow crush it to obtain the sodium-supplemented high-voltage hard carbon negative electrode material.
2. The preparation method according to claim 1, characterized in that: The hard carbon raw material in step (1) is at least one of coconut shell, palm, wood, resin and corn silk.
3. The preparation method according to claim 1, characterized in that: The time of the oxygen-free pre-calcination treatment in step (1) is 3-5 hours; the time of the high-temperature calcination is 3-4 hours.
4. The preparation method according to claim 1, characterized in that: The mass ratio of benzoyl peroxide, hydrogen peroxide and deionized water in step (2) is (0.06-0.1):(0.14-0.2):(0.72-0.78).
5. The preparation method according to claim 4, characterized in that: The mass ratio of the benzoyl peroxide, hydrogen peroxide and deionized water is 0.08:0.17:0.
75.
6. The preparation method according to claim 1, characterized in that: The inorganic sodium salt in step (2) is at least one of sodium carbonate or sodium hydroxide.
7. The preparation method according to claim 1, characterized in that: The mass ratio of the inorganic sodium salt to the hard carbon material in step (2) is (1-2):
100.
8. A sodium-supplemented high-voltage hard carbon negative electrode material prepared by the method according to any one of claims 1 to 7.
9. Use of the sodium-supplemented high-voltage hard carbon negative electrode material prepared by the method according to any one of claims 1 to 7 in sodium ion batteries.
10. A sodium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The active material used in the negative electrode is a sodium-supplemented high-voltage hard carbon negative electrode material prepared by the method described in any one of claims 1 to 7.